Sequencing of the tuf1 gene and the phosphorylation pattern of EF-Tu1 during development and differentiation in Streptomyces collinus producing kirromycin - Mikulík, K; Zhulanova, E (Biochemical and biophysical research communications, 1995)
We have cloned and sequenced the tuf1 gene from a kirromycin-producing strain of Streptomyces collinus. The gene encodes a polypeptide of 396 amino acid residues with a molecular weight of 43,849. The protein shows 97% identity with EF-Tu1 of S. coelicolor and is sensitive to kirromycin. EF-Tu-dependent translation of poly(U) was reduced to 50% in the presence of 0.25 microM kirromycin. Using high resolution two-dimensional electrophoresis and specific immunodetection with monoclonal antibodies we found that the EF-Tu1 is phosphorylated on threonine and that serine is the second phosphate-accepting amino acid. EF-Tu1 phosphorylated on threonine and serine residues was detected among the S150 supernatant proteins of vegetative cells, aerial mycelium and spores. The level of phosphorylated EF-Tu1 varied during the growth and differentiation.
Keywords: Peptide Elongation Factor Tu; Electrophoresis, Polyacrylamide Gel; imunosorpční techniky; Phosphorylation; DNA bakterií; sekvence nukleotidů; antibiotická rezistence; elektroforéza v polyakrylamidovém gelu; fosforylace; Sequence Analysis, DNA; Molecular Sequence Data; Pyridones; molekulární sekvence - údaje; Immunosorbent Techniques; Phosphothreonine; Escherichia coli; fosfothreonin; sekvenční analýza DNA; Amino Acid Sequence; DNA, Bacterial; Base Sequence; isoelektrická fokusace; elongační faktor Tu; Isoelectric Focusing; fosfoserin; pyridony; Drug Resistance, Microbial; Streptomyces; sekvence aminokyselin; Phosphoserine